KETERAMPILAN MENULIS FOLKLOR DENGAN MODEL MENYIMAK CERITA - Muliadi Muliadi; Kasma F. Amin (STAI Darul Qalam Tangerang, 2022)
This folkloric story writing skill aims to strengthen students' character education by instilling the value of national character contained in local regional stories. Another goal is to preserve oral stories as a wealth of the nation's local culture. The method of implementation is training and introduction to oral stories. This activity consists of several stages, namely planning, implementation. and evaluation. The first stage is to plan activities by compiling material that will be used in training. The second stage is the implementation which consists of activities to make a pre-test to find out students' understanding of local stories in their area before students are treated to oral stories. Furthermore, the activity of listening to stories and writing. The third stage is to evaluate the students' ability to write storylines and read back in front of the class. This activity involved 20 students and a teacher Indonesian as many as two people. The results of the activity showed about: 1) a reminder of students' understanding of the story title, characters, and local storylines of their area. 2) improving students' ability to write folklore plots. 3) after listening and writing skills training there is an increase in students' appeal to know more about their regional stories. 4) strengthening students' character education through folklore in their area has proven to have a significant improvement after several cycles of providing story material